2018
DOI: 10.1111/jfr3.12468
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up citizen initiatives as emergent actors in flood risk management: Mapping roles, relations and limitations

Abstract: The recent shift to individualisation of flood risk calls for a stronger involvement of private actors. Bottom‐up citizen initiatives (BUIs) may bring together governmental bodies with people at risk. Drawing on a screening of existing BUIs in Europe, North America, and Australia and an in‐depth analysis of three study sites, this paper maps BUI activities to stages in the risk management cycle and discusses the institutional, relational and social proximity between BUIs and other stakeholders. Flood BUIs ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 46 publications
0
44
0
3
Order By: Relevance
“…Implementing PLFRA measures focuses mainly on the individual household level because technical protection schemes are often understood as collective flood risk management strategies. The implication is that policy documents and academic research center on individuals and only in rare cases on collective actions and activities (Burns & Slovic, ; Seebauer, Ortner, Babcicky, & Thaler, ; Thaler & Seebauer, ). Consequently, the critical question focuses on what drives/motivates private people to adapt to flood hazards.…”
Section: Individual Motivations To Implement Plfra Measuresmentioning
confidence: 99%
“…Implementing PLFRA measures focuses mainly on the individual household level because technical protection schemes are often understood as collective flood risk management strategies. The implication is that policy documents and academic research center on individuals and only in rare cases on collective actions and activities (Burns & Slovic, ; Seebauer, Ortner, Babcicky, & Thaler, ; Thaler & Seebauer, ). Consequently, the critical question focuses on what drives/motivates private people to adapt to flood hazards.…”
Section: Individual Motivations To Implement Plfra Measuresmentioning
confidence: 99%
“…Research has found evidence of an emerging role of communities and citizens in local FRM (Edelenbos, Van Buuren, Roth, & Winnubst, 2017;Forrest et al, 2019;Geaves & Penning-Rowsell, 2015;Harris, Shaw, Scully, Smith, & Hieke, 2017;McEwen, Holmes, Quinn, & Cobbing, 2018;O'Brien, Ambrose-Oji, Morris, Edwards, & Williams, 2014a;Seebauer, Ortner, Babcicky, & Thaler, 2018). This increasing involvement of citizens is driven by both flood experiences and national policy agendas, such as the Participation Society in the Netherlands, that seek to stimulate citizens to be more active and willing to take a greater role in their local milieu (Seebauer et al, 2018;Verhoeven & Tonkens, 2013). The contributions and emerging roles of citizens in local FRM can have implications for local flood resilience and for more holistic FRM approaches that draw on broader knowledge and expertise than in the past (Forrest, Trell, & Woltjer, 2017;Forrest et al, 2019;McEwen et al, 2018;McEwen & Jones, 2012;O'Brien et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…This is the "bottom-up approach". Responsibilities and initiatives need to be well-balanced between local residents and the government [5]. As an international strategy, the Sendai Framework for Disaster Risk Reduction promotes resilience building using a top-down approach at the global level and disaster preparedness and early warning built up through a bottom-up approach at the community level [6][7][8].…”
Section: Introductionmentioning
confidence: 99%